Peran Guru PAI Dalam Membentuk Akhlak Mulia Siswa di SMA Al Islam Krian - Barkah, Achmad Afad El; Kamalia, Dinna; Asrofi, Muhammad Imam; Zamzami, M. Syifa Fairuz; Qomariyah, Galuh Fitri Ayu Nur; Majid, Amir Bandar Abdul; Roziq, Roziq (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The purpose of this study is to analyse the role of Islamic Religious Education (IRE) teachers in shaping the noble character of students at Al Islam Krian High School. This study uses a qualitative approach with a descriptive design. Data collection methods were carried out through direct and systematic observation of IRE learning activities, teacher and student interactions, and religious culture in the school environment. In addition, supporting data was obtained through documentation studies and literature reviews relevant to character education and morals from an Islamic perspective. The collected data was analysed using thematic analysis techniques, namely by grouping, interpreting, and drawing meaning from patterns of behaviour and learning strategies applied by PAI teachers. The results of the study indicate that PAI teachers have a strategic and multidimensional role in shaping students' noble morals, namely as moral role models, spiritual guides, and behavioural mentors. These roles are realised through exemplary attitudes, the habit of incorporating Islamic values into teaching and learning activities, the integration of worship practices into school culture, and continuous moral guidance. These findings confirm that the formation of noble character in students can be effective if supported by consistent exemplary behaviour from teachers, structured religious programmes, and a school environment conducive to the internalisation of Islamic values.